A core material for concrete and its application in ultra-high performance concrete

By using homemade water reducers and core materials of a variety of active powders in ultra-high performance concrete, the self-shrinkage and drying shrinkage problems of concrete in the early stages are solved, and the effects of high strength, low shrinkage and anti-chlorine ion penetration are achieved.

CN119118552BActive Publication Date: 2025-03-07THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411257856.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-07
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete is prone to self-shrinkage and dry shrinkage in the early stages, and existing solutions such as adding expansion agents or shrinkage agents have difficult-to-control the amount of dosage and are inconvenient for engineering applications.

Method used

It provides a core material for concrete, which is used in ultra-high performance concrete by mixing homemade water reducing agent with fly ash, ore powder, bauxite powder, nano calcium carbonate, alumina, zeolite powder, kaolin and other active powders, and improves its high strength, low shrinkage and anti-chlorine ion penetration under standard curing conditions.

Benefits of technology

It achieves the improvement of the compressive strength and chloride ion permeability of the concrete under standard curing conditions, reduces shrinkage, avoids cracking problems, and simplifies the construction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118552B_ABST
    Figure CN119118552B_ABST
Patent Text Reader

Abstract

The present invention discloses a core material for concrete and its application in ultra-high performance concrete, belonging to the technical field of concrete. The core material for concrete provided by the present invention comprises, by weight, 20 to 50 parts of fly ash, 20 to 40 parts of mineral powder, 20 to 30 parts of bauxite powder, 10 to 20 parts of nano calcium carbonate, 5 to 10 parts of alumina, 5 to 10 parts of zeolite powder, 5 to 10 parts of kaolin, and 8 to 30 parts of water reducing agent powder. The present invention provides a core material for concrete, which is obtained by mixing a self-made water reducing agent with active powders such as fly ash, mineral powder, bauxite powder, nano calcium carbonate, alumina, zeolite powder, and kaolin, and can be directly applied to ultra-high performance concrete during construction, so that the concrete can achieve the effects of high strength, low shrinkage, and resistance to chloride ion penetration under standard curing conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a core material for concrete and application thereof in ultra-high performance concrete. Background Art

[0002] Ultra-high performance concrete is a new type of concrete material, known as the most innovative cement-based composite material in recent years. It has excellent mechanical properties, durability and weather resistance, and is widely used in structures that require high strength, high durability and special engineering requirements. The compressive strength of ordinary concrete is generally between 20-50MPa, while UHPC is based on the principle of close packing, mixed with ultrafine minerals, high-strength aggregates and fiber reinforcements, and has a low water-cement ratio and optimized mix ratio, achieving the maximum density and minimum porosity of the material. Its compressive strength can usually reach more than 150MPa, and sometimes even more than 250MPa. Because UHPC contains a large amount of active admixtures, steam curing was initially used to completely release the active components in the cementitious material. Although this approach fully utilizes the active materials in UHPC, the steam curing process consumes a lot of manpower and material resources; in addition, cast-in-place steam curing is also affected by many problems such as site restrictions and electricity safety. Too much cementitious material and a low water-cement ratio will cause UHPC to easily shrink and dry and crack in the early stage. The existing solution is generally to add expansion agents or shrinkage reducers, but the process of expansion agents acting on concrete requires a large amount of water, which increases the difficulty of maintenance. In addition, expansion agents have the problem of delaying the formation of calcium sulfonate, and the dosage is difficult to control. Too much or too little dosage will not achieve the effect of reducing shrinkage and cracking. Another solution is to add shrinkage reducers such as alcohols and ethers to cement concrete. Commonly used ones include diols, triols and their homologues, ethylene glycol ethers, polyethylene glycol ethers, polyethylene glycol alkyl ethers, etc., but low molecular alcohols have a low boiling point and are volatile. They also have a pungent odor and a low ignition point. Most ethers are volatile and have a pungent odor, which is very inconvenient to use in actual engineering. In addition, chloride ions are also an important factor affecting the durability of concrete. Chloride ions have a special destructive effect on the passivation film on the surface of steel bars. When the chlorine content in concrete exceeds the standard, the steel bars will rust. The presence of water and oxygen is a necessary condition for the corrosion of steel bars. Therefore, if the concrete cracks, forming a channel for water and oxygen, the corrosion of the steel bars will be accelerated, causing the concrete cracks to further develop, the concrete protective layer to peel off, and ultimately the components to lose their bearing capacity.

[0003] In recent years, with the rapid development of water reducers, mineral admixtures have become one of the essential raw materials for concrete. When used with specific water reducers, they can improve the workability of concrete and ensure high strength, resistance to chloride ion corrosion and low shrinkage through the mechanisms of composite gelation effect, induced activation effect, surface microcrystallization effect, interface compatibility effect, and micro-aggregate effect. However, admixtures often use a variety of active components in combination, and on-site preparation has high requirements for construction units. Therefore, it is still necessary to develop a core material for concrete that is easy to add and can solve the problems of high strength, low shrinkage and resistance to chloride ion penetration under standard curing conditions. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a core material for concrete, which is obtained by mixing a homemade water reducer with active powders such as fly ash, mineral powder, bauxite powder, nano calcium carbonate, alumina, zeolite powder, kaolin, etc., and can be directly applied to ultra-high performance concrete during construction, so that the concrete can achieve the effects of high strength, low shrinkage and resistance to chloride ion penetration under standard curing conditions.

[0005] The technical solution for achieving the purpose of the present invention is as follows:

[0006] A core material for concrete, comprising, by weight, 20-50 parts of fly ash, 20-40 parts of mineral powder, 20-30 parts of bauxite powder, 10-20 parts of nano calcium carbonate, 5-10 parts of alumina, 5-10 parts of zeolite powder, 5-10 parts of kaolin, and 8-30 parts of water reducer powder, wherein the water reducer of the water reducer powder is copolymerized by monomer A, monomer B, monomer C, monomer D, and monomer E, and the general structural formula of the water reducer is shown in Formula 1:

[0007]

[0008] Among them, R1, R2, and R3 are respectively selected from one of H and CH3, and R4 is one of CH3 and CH2CH3; n is selected from any integer between 9 and 54, and the molar ratio of monomer A, monomer B, monomer C, monomer D, and monomer E is x:y:z:w:v=(2-4):(4-6):(3-5):(4-6):(2-3).

[0009] The monomer A of the water reducer is allyl polyethylene glycol ether, and the molecular weight of the allyl polyethylene glycol is 700-2000; the monomer B is acrylic acid or methacrylic acid; and the monomer D is sodium methacrylic acid or sodium propylene sulfonate.

[0010] The preparation method of the water reducing agent powder comprises the following steps:

[0011] S1. Synthesis of Monomer C: maleic anhydride and triethylene glycol monobutyl ether are dissolved in xylene, a catalyst is added, and the reaction is refluxed at 100-170° C. for 4-6 hours to obtain a reaction product, the reaction product solution is evaporated and concentrated to 40-60% of the original volume, isopropanol and a 80-90° C. supersaturated aqueous solution of NaCl are added, and the aqueous phase and the organic phase are extracted and separated, and the organic phase is subjected to vacuum rotary evaporation to obtain Monomer C triethylene glycol monobutyl ether maleate;

[0012] S2. Synthesis of monomer E: dissolve the silane coupling agent and triethylamine in tetrahydrofuran, slowly add them to the tetrahydrofuran solution of 1,5-hexadiene, stir in an ice-water bath for 5 to 10 minutes under a nitrogen atmosphere, then naturally warm to room temperature, continue stirring for 6 to 24 hours, and after the reaction is completed, vacuum rotary evaporation is performed to obtain monomer E;

[0013] S3. Under a nitrogen atmosphere, monomer D is dissolved in distilled water, heated to 70-90°C, and aqueous solutions of monomer A, monomer B, monomer C, and monomer E are slowly added dropwise, and an aqueous solution of an initiator is added dropwise at the same time. After the addition is completed, a constant temperature of 70-90°C is maintained for reaction for 5-10 hours, and then the temperature is lowered. An aqueous sodium hydroxide solution is added to adjust the pH to 7 to obtain an aqueous solution of a water reducer, which is freeze-dried to obtain a water reducer powder.

[0014] The catalyst in step S1 is p-toluenesulfonic acid, the molar ratio of maleic anhydride to triethylene glycol monobutyl ether is (2-3):1; the molar amount of the catalyst is 1-2% of the sum of the molar amounts of maleic anhydride and triethylene glycol monobutyl ether.

[0015] The silane coupling agent in step 2 is at least one of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, and the molar ratio of the silane coupling agent to 1,5-hexadiene is 1:(1.5-3).

[0016] The initiator in step S3 is at least one of potassium persulfate, ammonium persulfate and sodium persulfate, and the molar amount of the initiator is 0.5-5% of the sum of the molar amounts of monomers A-E.

[0017] The particle size of the zeolite powder is 100-1000 meshes, and the particle size of the alumina is 80-160 meshes.

[0018] Another object of the present invention is to protect the application of the concrete core material in ultra-high performance concrete.

[0019] Another object of the present invention is to provide an ultra-high performance concrete, comprising the following components: 600-1000 parts of cement, 100-300 parts of silica fume, 90-200 parts of core material for concrete, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-300 parts of steel fiber, and 100-200 parts of water.

[0020] The present invention also protects a method for preparing the ultra-high performance concrete, comprising the following steps: putting cement, silica fume, core material for concrete, fine aggregate and coarse aggregate into a mixer, dry mixing for 3-5 minutes, adding water and stirring evenly, then slowly adding and stirring for 3-5 minutes to form a uniform slurry, and finally slowly adding steel fiber and continuing stirring for 3-5 minutes, and discharging the material.

[0021] Beneficial Effects

[0022] The present invention provides a core material for concrete and its application in ultra-high performance concrete. The core material is used in combination with a self-made water reducing agent by a plurality of active powders, wherein the addition of zeolite powder can improve the fluidity and workability of concrete. The active silicon dioxide and aluminum oxide in the zeolite powder react with calcium hydroxide in cement to generate water-containing calcium silicate gel and calcium aluminate gel, thereby improving the degree of cement hydration, reducing porosity, and making the concrete structure denser, thereby improving the compressive strength and chloride ion penetration resistance of concrete. Alumina has a good anion adsorption effect, its zero point of charge is 8 to 8.5, has a large positively charged area, has a good electrostatic adsorption effect on negatively charged acid radical ions, can adsorb chloride ions in concrete, and reduce the diffusion of chloride ions in concrete. Bauxite powder contains a high aluminum content, which can improve the high temperature stability and chemical stability of concrete. Calcium carbonate can improve the fluidity and plasticity of concrete, avoid the influence of viscous components such as kaolin on the flowability of concrete, and calcium carbonate can also reduce the shrinkage rate of concrete, and improve the stability and durability of concrete. Kaolin has good adhesion, suspension and binding ability, which can improve the density of cement paste and reduce the penetration problem of chloride ions.

[0023] The homemade water reducer adds a small molecule triglycerol monobutyl ether monomer with a shrinkage functional group and a monomer containing a siloxane functional group that is more compatible with cement to the structure of the classic polycarboxylic acid water reducer to obtain a water reducer with a combing structure, in which the siloxane end is combined with the surface of the cement particles, and the steric hindrance structure of the polyether macromonomer end can hinder the approach of other cement particles, thus achieving high-efficiency dispersion. The esterified triglycerol monobutyl ether maleate contains functional groups of ether bonds, ester bonds and carboxyl groups, in which the ether bonds and ester bond segments can reduce the surface tension of the aqueous solution; the carboxyl group, as a hydrophilic and strongly polar group, can improve the dispersion and flow properties of cement particles. The sulfonate monomer is a strongly polar group and plays an important role in generating Zeta potential. The sulfonate monomer within a reasonable range can make the electrostatic repulsion of the water reducer reach the highest efficiency and achieve the optimal amount of water reducer adsorbed on the surface of cement particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The general structural formula of water reducing agent;

[0025] Figure 2is the H NMR spectrum of monomer C;

[0026] Figure 3 is the H NMR spectrum of monomer E;

[0027] Figure 4 Infrared spectrum of water reducing agent. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0030] The raw materials used in the embodiments and comparative examples are described as follows:

[0031] Fly ash: Raw fly ash was purchased from Guangzhou Yunhong Fly Ash Comprehensive Development Co., Ltd.;

[0032] Mineral powder: purchased from Huzhou Lanyun Ore Powder Co., Ltd.;

[0033] Bauxite powder: clinker bauxite, purchased from Xinmi Zhengyang Foundry Material Factory;

[0034] Nano calcium carbonate: 6000 mesh, purchased from Guangzhou Yuanda New Materials Co., Ltd.;

[0035] Alumina 1: high temperature alumina, 80-160 mesh, purchased from Shanghai Yuanjiang Chemical Co., Ltd.;

[0036] Alumina 2: activated alumina, 3-5 mm, purchased from Shanghai Yuanjiang Chemical Co., Ltd.;

[0037] Alumina 3: high-purity ultrafine alumina, 1250 mesh, purchased from Shanghai Yuanjiang Chemical Co., Ltd.;

[0038] Zeolite powder 1:300 mesh, feed grade zeolite powder, purchased from Ningbo Jiahe New Material Technology Co., Ltd.;

[0039] Zeolite powder 2:100 mesh, feed grade zeolite powder, purchased from Ningbo Jiahe New Material Technology Co., Ltd.;

[0040] Zeolite powder 3: 500 mesh, feed grade zeolite powder, purchased from Ningbo Jiahe New Material Technology Co., Ltd.;

[0041] Zeolite powder 4:1000 mesh, feed grade zeolite powder, purchased from Ningbo Jiahe New Material Technology Co., Ltd.;

[0042] Kaolin: purchased from Langfang Shuangma Chemical Co., Ltd.

[0043] Monomer A1: allyl polyethylene glycol, molecular weight 1000, model APEG-1000, purchased from Nantong Yuyuan New Materials Technology Co., Ltd.;

[0044] Monomer A2: allyl polyethylene glycol, molecular weight 700, model APEG-700, purchased from Nantong Yuyuan New Materials Technology Co., Ltd.;

[0045] Monomer A3: allyl polyethylene glycol, molecular weight 2000, model APEG-2000, purchased from Nantong Yuyuan New Material Technology Co., Ltd.;

[0046] Monomer B: acrylic acid, industrial grade, Jiangsu Pules Biotechnology Co., Ltd.;

[0047] Monomer C: Homemade, the preparation method is as follows: 3 equivalents of maleic anhydride and 1 equivalent of triethylene glycol monobutyl ether are dissolved in xylene, 0.06 equivalents of p-toluenesulfonic acid are added, and the reaction is refluxed at 130°C for 6 hours to obtain a reaction product, the reaction product solution is evaporated and concentrated to half of the original volume, isopropanol and a 90°C supersaturated NaCl aqueous solution are added, and the aqueous phase and the organic phase are extracted and separated, and the organic phase is subjected to vacuum rotary evaporation to obtain triethylene glycol monobutyl ether maleic anhydride monoester, and the obtained triethylene glycol monobutyl ether maleic anhydride monoester is measured by nuclear magnetic resonance, the instrument is AVANCE Digital 400NHz NMR of Bruker Company of Germany, the solvent is DMSO, and the obtained spectrum is shown as follows Figure 2 As shown, according to the molar ratio calculation, H1:H(2+3):H4:H5:H(6+7)=1:1.33:4.05:0.66:0.68, which is close to the theoretical value of 1:1.33:4:0.67:0.67, indicating that the monomer C triethylene glycol monobutyl ether maleate was successfully synthesized.

[0048] Monomer D: sodium methyl methacrylate sulfonate; 99.2%, purchased from Wuhan Rongcan Biotechnology Co., Ltd.;

[0049] Monomer E: Self-made, 2 equivalents of γ-mercaptopropyltrimethoxysilane and 0.23 equivalents of triethylamine were dissolved in tetrahydrofuran, and slowly added to a tetrahydrofuran solution of 2.5 equivalents of 1,5-hexadiene. The mixture was stirred in an ice-water bath for 5 min under a nitrogen atmosphere, and then naturally warmed to room temperature and continued to stir for 24 h. After the reaction was completed, the monomer E was obtained by vacuum rotary evaporation. The obtained monomer E was measured by nuclear magnetic resonance. The instrument was AVANCE Digital 400NHz NMR from Bruker, Germany. The solvent was deuterated chloroform. The obtained spectrum is shown as follows Figure 3 As shown, according to the molar ratio calculation, H1:H2:H3:H4:H5:H6:H7:H8=4.4:1:1:2.01:2.01:1:0.51:0.99, which is close to the theoretical value of 4.5:1:1:2:2:1:0.5:1, indicating that monomer E was successfully synthesized.

[0050] Water reducing agent powder: Homemade, preparation method is as follows:

[0051] Under nitrogen atmosphere, monomer D was dissolved in distilled water, heated to 85°C, and aqueous solutions of monomer A, monomer B, monomer C, and monomer E were slowly added dropwise, and an aqueous solution of ammonium persulfate was added dropwise at the same time. After the addition was completed, the temperature was kept at 85°C for 8 hours and then cooled. An aqueous solution of sodium hydroxide was added to adjust the pH to 7 to obtain an aqueous solution of a water reducer, which was freeze-dried to obtain a water reducer powder. The monomer molar ratio and weight average molecular weight of the water reducer are shown in Table 1, wherein the weight average molecular weight of the water reducer is obtained by gel permeation chromatography test. In addition, infrared spectroscopy test was performed on water reducer 3 using a Nexus Por Euro Fourier transform infrared spectrometer from Nicolet Company of the United States. The results are shown in Table 1. Figure 4 As shown, from Figure 4 It can be seen from the infrared analysis spectrum of water reducer that at 1580cm -1 and 1403.9cm -1 The asymmetric stretching vibration absorption peak and symmetric stretching vibration absorption peak of carbonyl C=O in carboxylate appeared at 1726cm -1 The C=O stretching vibration absorption peak in the ester appeared at 1351 cm -1 SO appeared 3- The characteristic absorption peak of stretching vibration is at 3419cm -1 The characteristic peak of OH appeared at 1170 cm -1 The COC ether bond stretching vibration peak appeared at 690 cm -1 The characteristic peak of Si-C appeared at 477 cm -1 The characteristic peaks of O-Si-O appeared.

[0052] Cement: Portland cement, PII 52.5R, produced by Yingde Conch Cement Co., Ltd.;

[0053] Silica fume: SiO2 with an average particle size of 0.1 to 0.3 μm, purchased from Guangdong Jusan Industrial Co., Ltd.;

[0054] Fine aggregate: machine-made sand, fineness modulus 2.8, produced in Jiangmen, Guangdong;

[0055] Coarse aggregate: diabase crushed stone, produced in Ganzhou City, Jiangxi Province, with a particle size of 5-8mm;

[0056] Steel fiber: end hook type steel fiber, SF100 / 60BP, purchased from Bolpais;

[0057] Water: Guangzhou tap water, in compliance with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006);

[0058] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0059] Table 1 Monomer molar ratio and weight average molecular weight of water reducer

[0060]

[0061] Core material 1~20

[0062] A core material for concrete, the specific composition of which is shown in Table 2.

[0063] Table 2 Components and weight parts of core materials

[0064]

[0065]

[0066] Table 2

[0067]

[0068]

[0069] Examples 1 to 12

[0070] Put 100 parts of core materials 1 to 12 of concrete into a mixer with 900 parts of cement, 100 parts of silica fume, 688 parts of fine aggregate and 534 parts of coarse aggregate, dry mix for 5 minutes, add 143 parts of water and stir evenly, then slowly add and stir for 5 minutes to form a uniform slurry, finally slowly add 156 parts of steel fiber and continue stirring for 3-5 minutes, discharge the material, and obtain high-performance concrete.

[0071] Embodiment 13

[0072] The preparation method is the same as that of Examples 1 to 12, except that the core material for concrete is core material 3, and the amount of core material 3 is 200 parts.

[0073] Comparative Examples 1 to 8

[0074] The preparation method is the same as that of Examples 1 to 12, except that the core material for concrete is core material 13 to 20.

[0075] Comparative Example 9

[0076] The preparation method is the same as that of Examples 1 to 12, except that the core material for concrete is core material 3, and the amount of core material 3 is 50 parts.

[0077] Comparative Example 10

[0078] The preparation method is the same as that of Examples 1 to 12, except that the core material for concrete is core material 3, and the amount of core material 3 is 300 parts.

[0079] Performance Testing

[0080] 1. Expansion test: After mixing, the concrete is left to stand for 60 minutes and tested in accordance with the national standard GB / T50080-2016;

[0081] 2. Shrinkage test: The concrete was made into a prism with a specimen size of 100mm×100mm×400mm. The test method was carried out in accordance with GB / T 50082-2009, and the shrinkage rate was calculated after 7d, 28d, and 365d after being taken out of the curing room;

[0082] 3. Compressive strength test: The concrete was made into a 100 mm cube specimen, and standard curing and steam curing were performed for 24 hours and 24 hours respectively. Then, the compressive strength of the concrete was tested for 28 days in accordance with the national standard GB / T 50081-2019, and the compressive strength of the concrete was compared between standard curing and steam curing.

[0083] 4. Chloride ion penetration resistance test: The concrete is made into a cylindrical component with a diameter of 100 mm and a height of 50 mm. After forming, it is covered with plastic film and moved to a standard curing room. The mold is removed within 24 hours and immersed in a water pool in the standard curing room for curing for 28 days. The test is carried out according to the RCM method of GB / T 50082-2009.

[0084] Table 4 Performance of Comparative Examples and Examples

[0085]

[0086] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A core material for concrete, characterized in that: The invention comprises 20 to 50 parts by weight of fly ash, 20 to 40 parts of mineral powder, 20 to 30 parts of bauxite powder, 10 to 20 parts of nano calcium carbonate, 5 to 10 parts of alumina, 5 to 10 parts of zeolite powder, 5 to 10 parts of kaolin, and 8 to 30 parts of water reducing agent powder. The water reducing agent of the water reducing agent powder is copolymerized by monomer A, monomer B, monomer C, monomer D, and monomer E. The general structural formula of the water reducing agent is shown in Formula 1: Among them, R1, R2, and R3 are respectively selected from one of H and CH3, and R4 is one of CH3 and CH2CH3; n is selected from any integer between 9 and 54, and the molar ratio of monomer A, monomer B, monomer C, monomer D, and monomer E is x:y:z:w:v=(2-4):(4-6):(3-5):(4-6):(2-3).

2. The core material for concrete according to claim 1, characterized in that: The monomer A of the water reducer is allyl polyethylene glycol, and the molecular weight of the allyl polyethylene glycol is 700-2000; the monomer B is acrylic acid or methacrylic acid; and the monomer D is sodium methacrylic acid or sodium propylene sulfonate.

3. The core material for concrete according to claim 1, characterized in that: The preparation method of the water reducing agent powder comprises the following steps: S1. Synthesis of Monomer C: maleic anhydride and triethylene glycol monobutyl ether are dissolved in xylene, a catalyst is added, and the reaction is refluxed at 100-170° C. for 4-6 hours to obtain a reaction product, the reaction product solution is evaporated and concentrated to 40-60% of the original volume, isopropanol and a 80-90° C. supersaturated aqueous solution of NaCl are added, and the aqueous phase and the organic phase are extracted and separated, and the organic phase is subjected to vacuum rotary evaporation to obtain Monomer C; S2. Synthesis of monomer E: dissolve the silane coupling agent and triethylamine in tetrahydrofuran, slowly add them to the tetrahydrofuran solution of 1,5-hexadiene, stir in an ice-water bath for 5 to 10 minutes under a nitrogen atmosphere, then naturally warm to room temperature, continue stirring for 6 to 24 hours, and after the reaction is completed, vacuum rotary evaporation is performed to obtain monomer E; S3. Under a nitrogen atmosphere, monomer D is dissolved in distilled water, heated to 70-90°C, and aqueous solutions of monomer A, monomer B, monomer C, and monomer E are slowly added dropwise, and an aqueous solution of an initiator is added dropwise at the same time. After the addition is completed, a constant temperature of 70-90°C is maintained for reaction for 5-10 hours, and then the temperature is lowered. An aqueous sodium hydroxide solution is added to adjust the pH to 7 to obtain an aqueous solution of a water reducer, which is freeze-dried to obtain a water reducer powder.

4. The core material for concrete according to claim 3, characterized in that: The catalyst in step S1 is p-toluenesulfonic acid, the molar ratio of maleic anhydride to triethylene glycol monobutyl ether is (2-3):1; the molar amount of the catalyst is 1-2% of the sum of the molar amounts of maleic anhydride and triethylene glycol monobutyl ether.

5. The core material for concrete according to claim 3, characterized in that: The silane coupling agent in step 2 is at least one of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, and the molar ratio of the silane coupling agent to 1,5-hexadiene is 1:(1.5-3).

6. The core material for concrete according to claim 3, characterized in that: The initiator in step S3 is at least one of potassium persulfate, ammonium persulfate and sodium persulfate, and the molar amount of the initiator is 0.5-5% of the sum of the molar amounts of monomers A-E.

7. The core material for concrete according to claim 1, characterized in that: The particle size of the zeolite powder is 100-1000 meshes, and the particle size of the alumina is 80-160 meshes.

8. Use of the core material for concrete according to any one of claims 1 to 7 in ultra-high performance concrete.

9. An ultra-high performance concrete, characterized in that: The concrete core material comprises the following components: 600-1000 parts of cement, 100-300 parts of silica fume, 90-200 parts of core material for concrete, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-300 parts of steel fiber and 100-200 parts of water. The core material for concrete is the core material for concrete according to any one of claims 1 to 7.

10. The method for preparing ultra-high performance concrete according to claim 9, characterized in that: The method comprises the following steps: putting cement, silica fume, core material for concrete, fine aggregate and coarse aggregate into a mixer, dry mixing for 3-5 minutes, adding water and stirring evenly, then slowly adding water and stirring for 3-5 minutes to form a uniform slurry, and finally slowly adding steel fiber and stirring for 3-5 minutes to discharge the material.

Citation Information

Patent Citations

  • Light low-shrinkage super-high performance concrete and preparation method thereof

    CN107935505A

  • Quaternary ammonium salt polyether ester monomer, EPEG type polycarboxylate water reducing agent, and preparation method therefor

    WO2024125545A1